Philosophical underpinnings in Jaun Elia's poetry: an exploration of coping mechanism in verses - Pathak S. (My University, 2025)
Jaun Elia, a prominent figure in Hindi and Urdu poetry, was a versatile personality known for his contributions as a poet and scholar. This article delves into the philosophical underpinnings of Jaun Elia's poetry, exploring themes of absurdism, alienation, and individualism as manifestations of his existential struggles. By employing thematic analysis, it delves into the intricate layers of thought within Elia's verses, revealing how poetry served as a coping mechanism for him amidst his perpetual anguish. Elia's work is examined as a testament to his resilience in the face of existential despair, shedding light on the ways in which he grappled with the inherent meaninglessness of existence. This study explains how Elia navigated his profound sense of isolation and pessimism, offering insights into the complex interplay between existential philosophy and poetic expression in his writings. © 2024 National Association for Poetry Therapy.